STAT TESTS SERVICE AND QUALITY CONTROL AT HAMAD MEDICAL CORPORATION DOHA - SATTARKHAN, A. (Journal of Ayub Medical College Abbottabad, 2001)
Background: The recognition and validity of laboratory results can better be judged by its internal and external quality control systems. Here we report an internal quality check of the stat service provided to the inpatients at Hamad Medical Corporation, Doha, State of Qatar. Methods: Periodic internal quality control of nine chemist) analyses, BUN, Na, K, Cl, Ca, Co2, Glucose. Creatinine and Bilirubin were made on auto-analyzer Astra VIII. BIORAD Normal and Abnormal (Chemistry Control) and immunoassay level l.2and 3 were employed. All results falling within 2 SD were accepted. Results: 2 SD% for chemistry Normal and Abnormal ranged from 61.5% to 85.5% and 92.0% to 98.8% and for hormones Immunoassay level 1.2. and 3 from 92.7% to 100% respectively.